Differences in cardiometabolic risk markers among ethnic groups in Queensland, Australia. (24th March 2019) - Gallegos, Danielle; Do, Hong; To, Quyen G.; Vo, Brenda; Goris, Janny; Alraman, Hana
Abstract: Very little is known about the cardiometabolic risk of migrants who settle in Australia. This study investigated differences in cardiometabolic risk markers among ethnic groups attending a tailored healthy lifestyle program in Queensland, Australia; and differences in these markers between those living in Australia for shorter versus longer periods of time. Baseline data collected between October 2014 and June 2017 from the Living Well Multicultural—Lifestyle Modification Program were used. People living in ethnic communities in Queensland who were ≥18 years old, and not underweight were eligible to participate. Independent variables were ethnicity and length of time in Australia. Outcomes were cardiometabolic risk markers including BMI, waist circumference, weight‐to‐height ratio (WHtR) and hypertension. Analyses were done separately for each independent variable. Linear and logistic regressions were run for continuous and binary outcomes with differences/Odds ratios reported respectively. Multivariable analyses showed that Burmese/Vietnamese had an average BMI lower than Afghani/Arabic (3.7 points), Somalian/Sudanese (4.7 points) and Pacific Islander (11.6 points) ( p < 0.001) respectively. Differences in waist circumference between Burmese/Vietnamese with Sri Lankan/Bhutanese, Afghani/Arabic, Somalian/Sudanese and Pacific Islander were 6.3, 8.4, 9.1 and 24.0 cm ( p < 0.01) respectively. Although Burmese/Vietnamese also had lower average WHtR compared to the others, the differences were not significant for Somalian/Sudanese. Moreover, Sri Lankan/Bhutanese and Pacific Islander were more likely to be hypertensive compared to Burmese/Vietnamese ( p < 0.05). Immigrants living in Australia >5years had on average 1.2 points higher BMI, 2.4cm larger waist circumference, and 0.02 points higher WHtR ( p < 0.05) compared to those living for ≤5 years. Long‐stay immigrants were also more likely to be hypertensive than short‐stay immigrants ( p < 0.01). In conclusion, cardiometabolic risk is significantly different among ethnic groups in Queensland with Pacific Islanders having the highest risk. Immigrants living in Australia >5 years had higher risks compared to those living in Australia for shorter periods of time.